Teachers' Strategies in Fostering Emotional Intelligence Among Grade X Students at SMAN 1 Kota Tangerang Selatan Through Contextual Learning - Pratama, Bintang Syawa; Tanenji, Tanenji (Fakultas Agama Islam Universitas Islam As Syafi'iyah, 2025)
This study aims to analyze the strategies of Islamic Education and Character (PAIBP) teachers in enhancing students’ emotional intelligence through contextual teaching and learning at SMA Negeri 1 Kota Tangerang Selatan. The research employed a mixed-method approach with an explanatory sequential design. Data were collected through observation, interviews, documentation, and questionnaires, and then analyzed using both qualitative descriptive and quantitative techniques. The findings reveal that PAIBP teachers implemented various strategies such as modelling, cooperative learning, role playing, and reflection to help students recognize, regulate, and develop their emotional intelligence. Supporting factors include teachers’ readiness to design relevant learning materials, supportive school environments, and adequate literacy resources. However, limited literacy among some students emerged as an obstacle in applying contextual learning effectively. Overall, this study highlights that contextual teaching significantly contributes to the development of students’ emotional intelligence and provides valuable insights for improving PAIBP instructional practices.